Enhanced Recovery After Spine Surgery: An analysis of the interventions that improve quality of patient care, recovery, and outcome - Borkotoky, Abhigyan; Ahmed, Shameem; Dutta, Deep (Nepal Journal of Neuroscience, 2001)
Introduction: The application of Enhanced Recovery After Surgery (ERAS) protocols in spine surgeries remain relatively underrepresented in the existing literature. Despite significant research efforts in this field, a consistent standardization of ERAS practices for spine surgeries has yet to be established. Material and Methods: We have successfully implemented an Enhanced Recovery After Surgery (ERAS) protocol across a range of spinal procedures. Our comprehensive ERAS protocol encompasses various key elements, such as minimally invasive surgery, avoidance of drains or catheters, multimodal analgesia, early initiation of enteral feeding, prompt mobilization and rehabilitation, and an emphasis on facilitating early patient discharge. These areas span from pre-hospitalization optimization to postoperative care, including monitoring patient satisfaction and tracking outcomes. Result: During a 100-day study period, 54 patients were enrolled in the investigation. The implementation of Multimodal Analgesia (MMA) resulted in a significant reduction in pain for all patients. However, four patients experienced Postoperative Nausea and Vomiting (PONV). Enteral feeding commenced four hours following anesthesia recovery, and mobilization was initiated approximately ten hours after the surgical procedure. Comprehensive rehabilitative care was introduced within 14 to 16 hours post-surgery. On average, patients remained in the hospital for approximately 29 hours. This approach demonstrates the potential for effective pain management and a relatively short hospital stay for patients undergoing this procedure. Conclusion: Efforts to implement ERAS principles in spinal procedures have shown promise, with some studies indicating potential benefits such as shorter hospital stays, reduced postoperative pain, and quicker return to daily activities.